Peran Biro Hukum Sekretariat Daerah Provinsi Bengkulu Dalam Proses Pembentukan Peraturan Daerah (Perda) Dengan Merujuk Pada Peraturan Gubernur Bengkulu Nomor 21 Tahun 2024 Tentang Kedudukan, Susunan Organisasi, Tugas Dan Fungsi Serta Tata Kerja Perangkat - Sumayah Fitri Yana; Almira Rahma Harningtyas; Alya Rahmadella; Hafidza Zia (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study examines in depth the role of the Legal Bureau of the Regional Secretariat of Bengkulu Province in the process of drafting Regional Regulations (Perda), referring to Bengkulu Governor Regulation Number 21 of 2024 concerning the Position, Organizational Structure, Duties and Functions, and Work Procedures of Regional Apparatus. This governor regulation provides a legal basis for the authority of the Legal Bureau as an implementing element of governmental affairs that holds strategic functions in planning, drafting, harmonizing, supervising, and documenting regional legal products. Using a normative–qualitative research method with statutory, conceptual, and documentation approaches, this study comprehensively analyzes the role of the Legal Bureau at each stage of Perda formation, starting from the formulation of the Regional Legislation Program (Prolegda), facilitation of academic paper preparation and draft regional regulations, implementation of horizontal and vertical harmonization, assistance in joint discussions with the Regional House of Representatives (DPRD), to the stages of promulgation, numbering, and documentation through the Regional Legal Documentation and Information Network (JDIH). The findings indicate that the Legal Bureau plays a highly decisive role in ensuring the quality of regional regulations, particularly by ensuring the conformity of draft regional regulations with the principles of statutory drafting and their consistency with national regulations. Nevertheless, several challenges—such as limited human resources with expertise in legislative drafting, suboptimal cross-agency coordination, and the workload associated with managing the JDIH—continue to hinder the effective execution of its functions. These findings emphasize the importance of institutional strengthening, capacity building for government personnel, and the development of digital systems to support the Legal Bureau’s effectiveness in the future.